Russian-Language Version of the Trail Making Test Implemented on the Inquisit Computer Platform - I.A. Fedotov; A.G. Faustova; A.A. Zaitseva; E.A. Fedotova; D.I. Shustov (Sovremennye tehnologii v medicine, 2026)
The aim of the study was to adapt and validate the Trail Making Test (TMT) implemented on the Inquisit computer platform. Materials and Methods. A total of 69 individuals were examined: 34 conditionally mentally healthy volunteers (12 men and 22 women; mean age 20.6 [20.1; 21.2] years) and 35 schizophrenia patients (12 men and 23 women; mean age 38.7 [34.1; 43.3] years). The test tasks and user interface of the original English-language TMT script were translated into Russian. The correctness of the translation was verified by the Inquisit platform developers, after which the Russian-language version was made available on the platform. The study (testing was performed twice) was conducted using the Russian-language TMT script, the Cancellation Test, the Number Finding Test (Schulte tables), and the 10-Word Learning Test. Results. Cronbach’s alpha coefficient was 0.96 for the conditionally mentally healthy group and 0.90 for the schizophrenia patient group, indicating sufficient internal consistency of the TMT. Quantitative measures of test-retest reliability reached noticeable to high levels on the Chaddock scale for time-based parameters, while no correlations were found for the number of errors. For both groups, positive statistically significant correlations were found between the time spent on the TMT and the Number Finding Test. In the schizophrenia patients, negative statistically significant correlations were found between the number of lines processed (Cancellation Test) and the time spent (TMT). These findings confirm convergent validity between TMT time scores, classical attention tests, and dynamic characteristics of thinking. At the same time, no significant correlations were found between the number of errors in the TMT and in the Cancellation Test. This might be related to different neuropsychological mechanisms underlying errors in these tests. Discriminant validity was demonstrated by the absence of significant correlations between most TMT measures and the results of the 10-Word Learning Test in both groups. Conclusion. The adapted TMT has sufficient internal consistency, convergent and discriminant validity, and test-retest reliability. Thus, it can be recommended for use in research to assess executive function deficits in schizophrenia patients. Notably, time spent on TMT tasks is the parameter that most closely corresponds to the assessment of dynamic attention indicators.